ЭКСТРАКОРПОРАЛЬНАЯ КОРРЕКЦИЯ В РАННЕМ ПОСЛЕОПЕРАЦИОННОМ ПЕРИОДЕ У БОЛЬНЫХ С ТЯЖЕЛОЙ ОСТРОЙ ИШЕМИЕЙ НИЖНИХ КОНЕЧНОСТЕЙ (World Science, 2019)
The clinical results of the use of Continuous Veno-Venous High Flux Dialysis (CVVHFD) in the early postoperative period in 37 patients with severe lower limb ischemia and an elevated preoperative level of blood creatinine were studied. The dynamics of total creatine phosphokinase, myoglobin, potassium in the early postoperative period was studied. The use of CVVHFD before the manifestation of the classic clinical presentation of renal dysfunction reduces the risk of adverse cardiopulmonary events from 26.1% to 14.3% and decreases the incidence of clinical renal dysfunction from 30.4% to 14.3%.